Low estimated glomerular filtration rate is associated with poor outcomes in patients who suffered a large artery atherosclerosis stroke. Issue 2 (April 2015) - Yeh, Shin-Joe; Jeng, Jiann-Shing; Tang, Sung-Chun; Liu, Chung-Hsiang; Hsu, Shih-Pin; Chen, Chih-Hung; Lien, Li-Ming; Lin, Huey-Juan; Chen, Chiu-Mei; Lin, Ruey-Tay; Lee, Siu-Pak; Lin, Ching-Huang; et al.
Abstract: Objectives: The relationship between low estimated glomerular filtration rate (eGFR) and the outcome of ischemic stroke remains controversial, despite the close association between kidney dysfunction and atherosclerosis. Methods: This study conducted subgroup analysis using data from the prospective Taiwan Stroke Registry to investigate the relationship between eGFR at the time of admission and 6-month functional outcomes in patients with the large artery atherosclerotic (LAA) subtype of acute ischemic stroke. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS), and outcomes were defined as modified Rankin Scale and mortality status at 6 months post stroke. Results: Of the 8052 patients with the LAA subtype of acute ischemic stroke in this study, 3312 (41.1%) had eGFR <60 mL/min/1.73 m 2 . The adjusted odds ratios of worse functional outcomes following a stroke were 1.10 (95% confidence interval [CI], 0.95–1.28), 1.60 (95% CI, 1.22–2.11) and 1.60 (95% CI, 1.10–2.33) in patients with eGFR 30–59, 15–29, and <15 as compared with those with eGFR 60–119 mL/min/1.73 m 2, respectively. Increased risk of mortality was closely and independently related to high NIHSS scores and low eGFR levels. Stroke severity and eGFR were also synergistically related to 6-month mortality, with an adjusted hazard ratio of 21.19 (95% CI, 9.69–46.35) in patients with NIHSS >15 and eGFR <15 mL/min/1.73 m 2, compared with those with NIHSS 0–5 and eGFR 60–119 mL/min/1.73 m 2 . Conclusions: Low eGFR was significantly and independently associated with 6-month functional outcomes and mortality in patients with the LAA subtype of acute ischemic stroke. The deleterious relationship between low eGFR levels and mortality following stroke was exacerbated by its synergistic association with stroke severity. Graphical abstract: Highlights: Kidney dysfunction was common in large artery atherosclerotic ischemic stroke. Low estimated glomerular filtration rate was associated with poor stroke outcomes. Kidney function and stroke severity had a synergistic association with mortality.